The Influence of Competence, Communication, Organizational Culture, and Training on Employee Performance - Sri Langgeng Ratnasari, Yuli Susilowati, Herni Widiyah Nasrul, Widodo Ismanto, Erwin Ashari (International Journal of Advanced Science and Technology, 2020)
Employee performance is one of the most important things in the organization, employee performance is a concern and must be improved anytime, because employee performance determines a company performance. Employees are one of the human resources who have a big role in the company’s performance, and become one of the spearheads of the company. Therefore, its performance must be improved and optimized from time to time so that its performance increases, if employee performance increases, the company’s performance also increases. This research aims to determine the influence of competency on employee performance, the influence of communication on employee performance, the influence of organizational culture on employee performance, the influence of training on employee performance and the influence of competence, communication, organizational culture, and training on employee performance. The population of this research is 154 employees of PT. AB with a research sample of 154 employees. The sampling technique uses census techniques. The analysis technique uses multiple linear regression analysis. The research method used is descriptive quantitative method. The results showed that competency had a significant influence on employee performance, communication had a significant influence on employee performance, organizational culture had a significant influence on employee performance, training had a significant influence on employee performance, as well as competence, communication, organizational culture, and training has a significant influence on employee performance.